Population Pharmacokinetics and Pharmacodynamic Target Attainment of Ampicillin in Neonates with Hypoxemic‐Ischemic Encephalopathy in the Setting of Controlled Hypothermia. Issue 4 (30th March 2017) - Cies, Jeffrey J.; Fugarolas, Keri N.; Moore, Wayne S.; Mason, Robert W.; Menkiti, Ogechukwu R.
Abstract : Study Objective: To describe the population pharmacokinetics and pharmacodynamic target attainment of ampicillin in neonates with hypoxic‐ischemic encephalopathy (HIE) undergoing controlled hypothermia (CH). Design: Prospective, open‐label pharmacokinetic study. Setting: A 189‐bed, freestanding children's tertiary care teaching hospital. Patients: Thirteen neonates (three females and 10 males) with HIE encephalopathy receiving CH and ampicillin 100 mg/kg/dose intravenously every 8 hours who were admitted to the neonatal intensive care unit between May 2013 and June 2014. Intervention: Blood (0.5 ml) was collected at 8, 10, and 14 hours of life coinciding with other scheduled laboratory investigations for ampicillin concentration analysis, providing a total of three ampicillin serum concentrations/patient. Measurements and Main Results: The patients had a median gestational age of 39 weeks, mean ± SD birth weight of 3.34 ± 0.61 kg, and mean ± SD estimated glomerular filtration rate of 43 ± 12.6 ml/minute/1.73 m 2 . Ampicillin concentrations were best described by a two‐compartment model with gestational age as a covariate with allometric scaling on total body clearance. The mean ± SD total body clearance for the population was 0.43 ± 0.12 ml/minute/kg (median 0.36 ml/min/kg), volume of the central compartment was 0.35 ± 0.46 L/kg, and the calculated population estimate for the total volume of distribution (Vd ) was 0.52 ± 0.28 L/kg. The R 2, bias, and precision were 0.497, 0.538, and 10.5 μg/ml and 0.972, −0.125, and 0.938 μg/ml for the observed versus population and observed versus individual predicted concentrations, respectively. Monte Carlo simulation was conducted to determine the probability of target attainment for 12 simulated ampicillin dosing regimens using 50% and 100% of the dosing interval that free drug concentration remains above the minimum inhibitory concentration ( f T > MIC) in 5000 simulated neonates with HIE receiving CH. Dosing regimens of 25 and 50 mg/kg/dose every 24 hours provided for an appropriate pharmacodynamic target attainment of 50% and 100% f T > MIC. Conclusion: To our knowledge, this study describes the first pharmacokinetic data of ampicillin in neonates with HIE receiving CH and demonstrates a reduced total body clearance and an increased Vd for ampicillin. Based on these data, modifications to the ampicillin dosing regimens seem appropriate during the period of CH. Dosing regimens of ampicillin 25 and 50 mg/kg/day were able achieve optimal probability of target attainment against all susceptible gram‐negative and gram‐positive bacteria in a population of neonates with HIE receiving CH for 50% and 100% f T > MIC.